Taking Construction Grammar One Step Further: Families, Clusters, and Networks of Evaluative Constructions in Russian - Endresen, Anna; Janda, Laura Alexis (Frontiers in Psychology, 2020)
We present a case study of grammatical constructions and how their function in a single language (Russian) can be captured through semantic and syntactic classification. Since 2016 an on-going joint project of UiT The Arctic University of Norway and the National Research University Higher School of Economics in Moscow has been collecting and analyzing multiword grammatical constructions of Russian. The main product is the Russian Constructicon (https://site.uit.no/russian-constructicon/), which, with over two thousand two hundred constructions (and more being continuously added), is arguably the largest openly available constructicon resource for any language. The combination of this large size with depth of analysis, containing both syntactic and semantic tags, makes it possible to view the interrelation of constructions as families and to discover trends in their behavior. Our annotation includes 53 semantic tags of varying frequency, with three tags that are by far more frequent than all the rest, accounting for 30% of the entire inventory of the Russian Constructicon. These three semantic types are Assessment, Attitude, and Intensity, all of which convey a speaker’s evaluation of a topic, in contrast to most of the other tags (such as Time, Manner, and Comparison). Assessment and Attitude constructions are investigated in greater detail in this article. Secondary semantic tags reveal that negative evaluation among these two semantic types is more than twice as frequent as positive evaluation. Examples of negative evaluations are: for Assessment VP tak sebe , as in Na pianino ja igraju tak sebe “I play the piano so-so [lit. thus self]”; for Attitude s PronPers-Gen xvatit/xvatilo (NP-Gen) , as in S menja xvatit “I’m fed up [lit. from me enough].” In terms of syntax, the most frequent syntactic types of constructions in the Russian Constructicon are clausal constructions [constituting an independent clause like s PronPers-Gen xvatit/xvatilo (NP-Gen) ] and constructions with the anchor in the role of adverbial ...